To the questions about the social purpose of state - Пильгун, Наталія Василівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2011)
It is consider various scientific approaches to the definition and nature of the social state, its social mission. It is explain basic mechanism of the social state